Answer:
none
Explanation:
We can start by multiplying both side of the equation by 6 in order to remove the fractions.
![6*(x+3)/(3) = 6(5 - (x-3)/(6))](https://img.qammunity.org/2022/formulas/mathematics/middle-school/fi4enj7op6428sxt931mnua61ijw08sjsw.png)
![2(x + 3) = 30 - 6*(x-3)/(6)](https://img.qammunity.org/2022/formulas/mathematics/middle-school/s9juqgwsrrzlsg9zapgmyox9qg0iaujv7e.png)
![2x + 6 = 30 -(x - 3)](https://img.qammunity.org/2022/formulas/mathematics/middle-school/fc3gu44hxgml9eou73hdjbn1fohligty8c.png)
![2x + 6 = 30 - x + 3](https://img.qammunity.org/2022/formulas/mathematics/middle-school/2wx1u6xpeu3g16kwutzf47076m40ai1f87.png)
Now, we can try to see if this equation is equivalent to the other options.
Every option has the left side as 2x - 6. In order to get that, we need to subtract 12 on both sides:
![2x - 6 = 30 - x + 3 - 12](https://img.qammunity.org/2022/formulas/mathematics/middle-school/kh0mog9o5r14p6lqgd7j2b9f5k22alnx8i.png)
This simplifies to
![2x-6 = 18 - x + 3](https://img.qammunity.org/2022/formulas/mathematics/middle-school/wokpd60mbpt7y65yfmu0s7z4bzo38x00s4.png)
This is not the same as any of the options shown.
We can check this by solving the equations.
2x - 6 = 18 - x + 3
3x = 6 + 18 + 3
3x = 27
x = 9
Now, the first option:
2x - 6 = 10 - x - 3
3x = 6 + 10 - 3
3x = 13
x = 13/3
The second option is the exact same as the third, so they would have the same solution:
2x - 6 = 30 - x- 3
3x = 6 + 30 - 3
3x= 33
x = 11
Since none of the options have the answer 9, they are not equivalent to the equation shown.